Consumer discrimination of Chemlali and Arbequina olive oil cultivars according to their cultivar, geographical origin, and processing system. Issue 7 (25th June 2014) - Hassine, Kaouther Ben; El Riachy, Milad; Taamalli, Amani; Malouche, Dhafer; Ayadi, Mohamed; Talmoudi, Khouloud; Aouini, Maroua; Jlassi, Yosra; Benincasa, Cinzia; Romano, Elvira; Perri, Enzo; Kiristakis, Apostolos; et al.
<x xml:space="preserve">Abstract</x> The chemical composition and consumer preferences according to consumer characteristics of virgin olive oils (VOOs) from "Chemlali" and "Arbequina" cultivars were studied in relation to processing system and geographical origin. Statistical analyses revealed significant differences (p < 0.05) among cultivars in % free acidity, K270, and OSI values, pigments, and antioxidant content and in some FAME content. Significant differences were also found according to the processing system in terms of some quality indices, pigments, antioxidant compounds, and OSI values. The effect of processing system on fatty acid composition was almost not significant except for some of them. The effect of the geographical origin was different in relation to the cultivars: For "Chemlali" cultivar, it was significant (p < 0.05) in all studied parameters except for acidity and total polar phenol content. However, for "Arbequina", the effect was significant (p < 0.05) for K232, pigments, antioxidant compounds and fatty acid composition except for margaric, margaroleic, linolenic, arachidic, and behenic fatty acids. Consumers were able to discriminate between cultivars with more preference for "Arbequina" oil, but only in case of "Chemlali" they could discriminate between the oils from different locations, with significantly more consumer liking for oils from Sidi Bouzid and Sawef. However, they were not able to discriminate between the processing systems. <inline-graphic xlink:href="ark:/27927/pghntzxn5d" content-type="ejlt201300254-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> A session of sensory analysis that shows consumer preferences according to consumer characteristics. Consumer preferences are defined as the subjective (individual) tastes and flavors, as measured by the satisfaction that a consumer derives from the consumption of different goods, in this study, the Virgin Olive Oil (VOO). VOO sensory analysis permits the consumer to rank the different oils according to the levels of satisfaction they give the consumer.